PENGARUH DEBT TO EQUITY RATIO, EARNING PER SHARE, PRICE EARNING RATIO, RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ 45 TAHUN 2014-2016 - Desty Rachmawati, 13.05.52.190; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze influence Debt to Equity Ratio (DER), Earning Per Share (EPS), Price Earning Ratio (PER), Return On Asset (ROA) to the price of shares listed on the company LQ 45. The population in this study are all companies listed on the Indonesia Stock Exchange joined in the Company LQ 45 in 2014-2016. The sampling technique was done by purposive sampling. Based on the purposive sampling obtained a sample of 135 companies for 3 years and was elected to the study sample as many as 93 companies. The data anlysis technique used is multiple regression analysis. The reesults showed that each variable has a different effect, namely Debt to Equity Ratio, Earning Per Share and Price Earning Ratio provide a positive and significant effect on stock price. Return on Asset a negative influence on stock. The conclusion of this study indicate that the regression model is formed by the independent variable Debt to Equity Ratio (DER), Earning Per Share (EPS), Price Earning Ratio (PER), Return on Asset (ROA) can be used to predict the price of shares in the publicly traded company listed on the Indonesian Stock Exchange (BEI) in the Company LQ45.Keywords: Debt to Equity (DER), Earning Per Share (EPS), Price Earning Ratio (PER), Return on Asset (ROA), and Stock Price